Effects of Rhizobium inoculum compared with mineral nitrogen fertilizer on nodulation and seed yield of common bean. A meta-analysis - dos Santos Sousa, Westefann [UNESP]; Soratto, Rogério Peres [UNESP]; Peixoto, Devison Souza; Campos, Thiago Souza [UNESP]; da Silva, Maryelle Barros [UNESP]; Souza, Ane Gabriele Vaz [UNESP]; Teixeira, Itamar Rosa; Gitari, Harun Ireri (Springer Nature, 2022)
Common bean (Phaseolus vulgaris) is one of the most important legumes for human consumption. It is highly adaptable to different edaphoclimatic conditions, being an important crop in addressing global food security challenges. The common bean production segment has undergone an intense technological advance, with a focus on the use of technologies to increase the availability of nitrogen (N) and the crops’ seed yield, while enhancing economic and ecological sustainability. Based on this, the present meta-analysis aimed to evaluate the effects of Rhizobium inoculation (RI), in comparison with mineral-N fertilization (NF), on the main nodulation characteristics, yield components, and seed yield of common beans. This study represents the largest assessment yet on this topic. We used data from peer-reviewed publications and, after extensive bibliographic research, analyzed 68 studies from seven countries. We found that RI increased seed yield (32.96%) but not to the same extent as NF. The RI is on average 12.31% less efficient than NF; however, when we categorized the factors, such as the time of year when common beans were grown, the soil management system, and the soil physicochemical characteristics, the RI effects were more promising. Here we show for the first time that RI was more efficient than NF when common beans were cultivated in the dry season, under a no-tillage system, and in soils with high organic matter content, with a potentially positive impact on yields. In addition, the difference in the efficiencies of RI and NF was attenuated when common beans were grown in soils with a clay texture, eutrophic, with low to neutral acidity, and with an adequate phosphorus availability, and using at least 10 g of rhizobial inoculum per kg of seeds.
Keywords: Biological nitrogen fixation; Inorganic fertilization; Phaseolus vulgaris; Sustainable agriculture; Symbiotic interaction